C-Fos immunoreactivity in the hypothalamus and reward system of young rats after social novelty exposure. Issue 7 (1st May 2019) - Gómez-Gómez, Yvette M.; Sánchez-Aparicio, Pedro; Mejía-Chávez, Sara; García-García, Fabio; Pascual-Mathey, Luz I.; Aguilera-Reyes, Ulises; Galicia, Oscar; Venebra-Muñoz, Arturo
Abstract : Socialization is an adaptive behavior during the early stages of life because it helps young animals become independent and determines healthy adult social behavior. Therefore, it is probable that the brain areas involved in the processing of social stimuli are more sensitive to social novelty during early life stages. To test this hypothesis, four groups of young male rats were exposed to different socioenvironmental stimuli; nonsocial physical novelty, social familiarity, social novelty, and a control group which received no stimulation. After stimuli exposure, brains were fixed and cut in coronal sections for c-Fos immunohistochemistry. The number of c-Fos-immunoreactive (c-Fos-ir) neurons in the paraventricular nucleus and supraoptic nucleus, the main producers of oxytocin and vasopressin, was compared, as well as in the nucleus accumbens and ventral pallidum, the main areas involved in reinforced behavior. A significantly higher number of c-Fos-ir neurons were found in animals exposed to social novelty in all areas, except in the supraoptic nucleus. In particular, the increase in c-Fos-ir in the paraventricular nucleus seems to be selective in response to social novelty, while the increase of c-Fos-ir in the nucleus accumbens and ventral pallidum suggests that social novelty during youth is a highly rewarding stimulus compared with social familiarity and nonsocial physical novelty.